Realitas Pendidikan Islam dan pandangan Filosofis Tokoh Pendidikan Islam Indonesia - Azis, Ardianto; Yusuf, Yusuf; Amin, Amin (RELIGI: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the reality of Islamic education in Indonesia through a philosophical approach by exploring the perspectives of prominent Indonesian Islamic education figures. The research method employed is library research with descriptive-qualitative analysis, focusing on the works, thoughts, and contributions of figures such as Ki Hajar Dewantara, KH. Ahmad Dahlan, and KH. Hasyim Asy’ari. The findings indicate that Islamic education in Indonesia is rooted in Islamic values combined with local wisdom and national spirit, creating a unique educational system that remains relevant to contemporary developments. The novelty of this research lies in its integration of philosophical analysis with the practical realities of education, offering a comprehensive perspective on the direction, challenges, and opportunities of Islamic education in Indonesia.